Secondary Surgery in Facial Feminization: Reasons and Recommendations. Issue 6 (December 2022) - Rochlin, Danielle H.; Chaya, Bachar F.; Rodriguez Colon, Ricardo; Onuh, Ogechukwu; Rojas, Allison; Rodriguez, Eduardo D.
Abstract : Background: As facial feminization surgery (FFS) continues to grow in access and popularity, the need for secondary FFS can be expected to increase. The purpose of this study was to identify reasons for FFS reoperation and offer recommendations to minimize secondary surgery. Methods: A retrospective cohort study of patients who underwent FFS from October 2017 to 2021 was performed. Patients who underwent nonstaged secondary surgery were identified and sorted in 2 non–mutually exclusive surgical cohorts: additional surgery, defined as unplanned additional feminization surgery on previously unoperated facial units, and revision surgery, defined as redo surgery on previously operated facial units. Reasons for secondary surgery were examined in the context of the senior author's experience. Results: Of 161 patients who underwent FFS, 41 (25.5%) underwent secondary surgery consisting of additional surgery (n = 32) and/or revision surgery (n = 30). There were no significant differences in clinical or demographic data between the secondary surgery and total FFS cohorts. Among additional surgery patients, facial units that had been previously operated on were as follows: nose (46.3%), trachea (31.7%), forehead/brow (22.0%), chin (12.2%), lips (9.8%), and cheeks (7.3%). Among revision patients, facial units revised were as follows: nose (36.6%), forehead/brow (26.8%), cheeks (17.1%), chin (17.1%), lips (12.5%), and trachea (2.4%). The main indication for revision for all facial units was undercorrection to feminine ideals. Conclusions: One-quarter of patients who underwent FFS had prior FFS and/or sought revision. Keeping in mind that the dominant indication for revision was undercorrection, FFS surgeons can minimize the need for secondary surgery in the future.